Helicobacter pylori and Hematologic Diseases - Sam Ryong Jee (Yong Chan Lee, 2020)
Helicobacter pylori (H. pylori) is a Gram-negative spiral bacterium, classified as a group 1 carcinogen by the World Health Organization. H. pylori infection is a major cause of gastritis, gastric and duodenal ulcers, and gastric cancer. It is associated with the pathogenesis of several hematologic diseases. H. pylori eradication has been proven effective in gastric mucosa-associated lymphoid tissue lymphoma and primary immune thrombocytopenia. As H. pylori causes iron deficiency anemia via several mechanisms, some recent guidelines recommended its eradication from patients with iron deficiency anemia. There are discussions of other conditions that are not included in the international consensus and management guides on H. pylori, including monoclonal gammopathy, myelodysplastic syndrome, childhood leukemia, coagulation disorder, megaloblastic anemia, pernicious anemia, plasma cell dyscrasia, and Henoch-Schönlein purpura. Further studies are required to establish new strategies to improve the management of patients with an infection combined with a hematologic disease of controversial or peculiar association.